2020
DOI: 10.1016/j.jobcr.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography of the masticatory muscles during chewing in different head and neck postures - A pilot study

Abstract: The objectives of this pilot study were to analyze the electromyography (EMG) activity of masseter and anterior temporalis muscles during chewing in 2 different posture conditions: natural head posture (NHP) and maximum yet comfortable forward head posture (FHP) in healthy individuals; and to compare EMG activity between subjects based on their NHP during chewing. Methods: Fifteen subjects participated. Sagittal head posture in sitting position was clinically assessed using a plumb line. Participants were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…In addition, the denture use group had lower neck muscle strength than the non-denture group. These findings support the previously described association between denture use and natural head position in older adults [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the denture use group had lower neck muscle strength than the non-denture group. These findings support the previously described association between denture use and natural head position in older adults [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…The subjects sat against the wall, keeping the spine upright, using the wall as a vertical reference, with both hands placed on top of their legs and feet on the ground. The subjects were asked to adjust their heads to the neutral position, with the mandible naturally relaxed (21). NHP is readily determined by a lateral photograph to visually assess the alignment of tragus of the ear related to the midline of trunk (21).…”
Section: Head Positionsmentioning
confidence: 99%
“…Moreover, only two studies have F I G U R E 2 Kinematic results (means and standard errors) of temporomandibular joint (TMJ), including ranges of maximum mouth opening (MMO), protrusion, lateral movement and condylar path length (CPL) in the healthy controls (C) and patients with nonspecific chronic neck pain (NP), *Significant group effect in CPL (p = .02) investigated the activity of masticatory muscles in individuals with neck pain or with the forward head posture. 48,49 They found that compared with healthy controls, individuals with neck pain or the forward head posture showed normal AT activation during maximum clenching. 48,49 However, by using high-density surface EMG, patients with moderate neck disability demonstrated increased activation of MA during submaximal clenching (30%-70% of maximum clenching).…”
Section: Discussionmentioning
confidence: 99%